2019
DOI: 10.1542/peds.2018-2758
|View full text |Cite
|
Sign up to set email alerts
|

Family Chaos and Asthma Control

Abstract: OBJECTIVES: Asthma is a highly prevalent childhood chronic disease, with particularly high rates among poor and minority youth. Psychosocial factors have been linked to asthma severity but remain poorly understood. This study examined (1) relationships between parent and child depression and posttraumatic stress disorder (PTSD) symptoms, family functioning, and child asthma control in a sample of urban minority youth with uncontrolled asthma and (2) family functioning as a pathway linking parent depression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…In line with the previous DSM-IV indications, studies on this issue were mainly on cancer diseases and, to a lesser extent, on traumatic accidents. It has only been in the last few years that other diseases have emerged [24][25][26][27][28][29].…”
Section: State Of the Artmentioning
confidence: 99%
“…In line with the previous DSM-IV indications, studies on this issue were mainly on cancer diseases and, to a lesser extent, on traumatic accidents. It has only been in the last few years that other diseases have emerged [24][25][26][27][28][29].…”
Section: State Of the Artmentioning
confidence: 99%
“…43,44 In a cross-sectional study of 223 primarily Hispanic children and adolescents with uncontrolled asthma, depressive symptoms in the parent and her or his child were associated with worse asthma severity or control, activity limitations, and emotional triggers of asthma. 45 Moreover, family chaos (measured by assessing commotion, disorganization, and routine in the household 46 ) was associated with worse asthma control (even after adjusting for depressive symptoms in both parent and child) and identified as a mediator of the association between parent-child depressive symptoms and worse asthma outcomes. 45 Adverse experiences in an individual's household can be highly stressful and have a long-lasting impact on an adolescent.…”
Section: Family-level Stressorsmentioning
confidence: 98%
“…45 Moreover, family chaos (measured by assessing commotion, disorganization, and routine in the household 46 ) was associated with worse asthma control (even after adjusting for depressive symptoms in both parent and child) and identified as a mediator of the association between parent-child depressive symptoms and worse asthma outcomes. 45 Adverse experiences in an individual's household can be highly stressful and have a long-lasting impact on an adolescent. A crosssectional study of 6 home adverse childhood experiences (ACE) and lifetime asthma prevalence in 92,472 children and adolescents (aged 0-17 years) in the United States revealed that home ACE were significantly associated with increased odds of lifetime asthma, with a dose-response relationship going from 1 ACE (OR ¼ 1.28, 95% CI ¼ 1.12-1.43) to 4 ACE (OR ¼ 1.73, 95% CI ¼ 1.27-2.36).…”
Section: Family-level Stressorsmentioning
confidence: 98%
“…Attention is more recently being given to the importance of household chaos on child health outcomes traditionally associated with health behavior research and public health. For example, greater household chaos has been independently related to poor asthma control among children and adolescents [5] and poor glycemic control among adolescents with type 1 diabetes [6]. Household chaos has also been identified as a potential obesity risk factor during infancy [7] and childhood [8].…”
mentioning
confidence: 99%